KESADARAN HUKUM DALAM PRAKTIK PENCATATAN PERKAWINAN: STUDI DI KABUPATEN BANGKALAN - Dewi Balqis Maharani; Saifullah; Abd. Rouf (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2026)
The practice of unregistered marriages is still widely found in society, including in Bangkalan Regency. In general, people tend to prioritize the religious validity of marriage rather than its registration by the state. This study aims to examine the practice of unregistered marriages and the factors influencing it, as well as to analyze the level of public legal awareness regarding marriage registration based on Soerjono Soekanto’s theory of legal awareness and al-Syāṭibī’s theory of maqāṣid al-syarī‘ah. This research is an empirical legal study using a sociological approach. The data sources were obtained through interviews and documentation. The data were analyzed using descriptive qualitative methods. The results show that the practice of unregistered marriages in Bangkalan Regency is influenced by the community’s legal culture, religious understanding, economic factors, educational background, and certain circumstances. Based on Soerjono Soekanto’s theory of legal awareness, the indicators of legal knowledge, legal understanding, and legal attitude have been fulfilled. However, the indicator of legal behavior has not been fully achieved because some people still do not officially register their marriages. From the perspective of al-Syāṭibī’s maqāṣid al-syarī‘ah, marriage registration aims to preserve religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl) as a form of protection for family welfare.